Analisis Sistem Pengolahan RME Rawat Jalan Di Rumah Sakit - Nani Yuniar; Fifi Nirmala G; Nurul Muflihah; Bunga Julvana Lumele; Dian Maharani; Fadhilah Salsabilah; Huriatul Jannah; Indah Cahaya Pratiwi; Muhammad Bagus Yahya; Laode Rifaldy Rizqi Ramadan.M; Nanda Visca Pradiny; Waode Heny Herdiana (CV. ITTC INDONESIA, 2025)
This study aims to review the processing system of Electronic Medical Records (EMR) in outpatient services at hospitals through a literature review of 10 journals published in the last five years. The analyzed literature indicates that EMR implementation has a positive impact on service efficiency, data accuracy, and user satisfaction. However, several challenges remain, including infrastructure readiness, staff training, and system integration. This study provides a comprehensive overview of the supporting and inhibiting factors in EMR implementation and offers recommendations that can serve as a reference for improving medical data processing systems in the future.